Crystal structure and molecular dynamics studies of L-amino acid oxidase from Bothrops atrox. (15th March 2017) - Feliciano, Patricia R.; Rustiguel, Joane K.; Soares, Ricardo O.S.; Sampaio, Suely V.; Cristina Nonato, M.
Abstract: L-amino acid oxidases (LAAOs) are dimeric flavoproteins that catalyze the deamination of L-amino acid to α-keto acid, producing ammonia and hydrogen peroxide. In this study, we report the crystal structure and molecular dynamics simulations of LAAO from the venom of Bothrops atrox (BatroxLAAO). BatroxLAAO presents several biological and pharmacological properties with promising biomedical applications. BatroxLAAO structure contains the highly conserved structural pattern of LAAOs comprising a FAD-binding domain, substrate-binding domain and helical domain, and a dimeric arrangement that can be stabilized by zinc. Also, molecular dynamics results show an asymmetric behavior, and a direct communication between FAD- and substrate-binding domains of counterpart subunits. These findings shed light on the structural role of dimerization to catalytic mechanism of SV-LAAOs. Highlights: The crystal structure of L-amino acid oxidase from Bothrops atrox was solved at 2.3 Å resolution. A zinc binding site identified at the dimeric interface may influence the stability of its quaternary structure. Positively charged grooves are found in the majority of SV-LAAOs in the opposite face of the active site. MD simulations reveal asymmetry between the dynamic behavior of the two monomers. Substrate binding induces a crosstalk between BatroxLAAO FAD- and substrate binding domains of counterpart chains.